Isolation and typing of Clostridium botulinum from milk powder of an enterprise associated with a case of infant botulism - LUO Haipeng; QU Hongren; DING Bo; REN Xiu; ZHAO Linna; BAI Jichao; WANG Yaping; LIN Lan; CUI Shenghui (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveThe aim of this study was to detect botulinum toxin and Clostridium botulinum （C.botulinum） in 30 batches of infant formula milk powder obtained from an enterprise and to analyze the whole genome of the strain of C. botulinum type B isolated from the samples.MethodsThe samples were subjected to C. botulinum isolation and botulinum toxin typing experiments according to the “National standard for food safety microbiological examination of C. botulinum and botulinum toxin” （GB 4789.12—2016）. The whole genomes of the isolated strains were sequenced and their genetic characteristics were analyzed.ResultsBotulinum toxin was not detected in any of the 30 batches of samples. After intraperitoneal injection of the enrichment solution into mice， four batches of milk powder samples induced symptoms of botulism， but C. botulinum was isolated from only one batch of milk powder samples. Genome sequencing revealed that the bacterium was C. botulinum group Ⅰ， type B， the toxin gene cluster was type Ha， and the toxin gene was subtype B2.ConclusionThe detection of C. botulinum in infant formula milk powder with a complex background of microorganisms should not be based on the isolation of bacteria as the gold standard but should be confirmed by a mouse toxicity test of the enrichment solution combined with a botulinum toxin antiserum protection test. Whole genome sequencing can accurately identify strains and analyze relevant genetic characteristics， providing reliable technical support for handling poisoning events.